The Impact of Logo Shapes Redesign on Brand Loyalty and Repurchase Intentions through Brand Attitude - Rafiq, Muhammad Rashid; Hussain, Rai Imtiaz; Hussain, Shahbaz (International Review of Management and Marketing, 2020)
The present research intends to investigate the effect of logo shapes redesign on brand loyalty and repurchase intention. The analysis also explores the mediating role of brand attitude between logo shapes redesign, brand loyalty, and repurchase intentions. This analysis utilized convenient non-probability sampling and gathered statistics from 452 students and teachers of the University of Okara, Pakistan. The data collected for the study were analyzed using Smart PLS3.0 and reliability analysis / Cronbach’s alpha was undertaken to determine the question’s accuracy and validity. The logo shapes redesign reviews significantly effect on brand attitude, further on brand loyalty and also on repurchase intention. Noticeably, logo shapes redesign is strongly related to brand loyalty and repurchase intentions both directly and indirectly. Brand attitude significantly mediates the connection between redesign logo shapes, brand loyalty, and repurchase intentions. Very few studies have explored the relationship between the redesign of logo shapes and brand attitude. Relevantly, the research is the first to demonstrate that a brand’s features (e.g. logo) may have a differential effect on consumer reaction based on brand loyalty and repurchase intentions to such an extent those loyal consumers often respond more positively than redesigned logos and repurchase product. Moreover, the research offers prolific implications for loyal customers in the study context. Keywords: Logo shapes redesign, brand attitude, brand loyalty, and repurchase intentions JEL Classification: M310 DOI: https://doi.org/10.32479/irmm.10308